SIRT3 alleviates imiquimod-induced psoriatic dermatitis through deacetylation of XBP1s and modulation of TLR7/8 inducing IL-23 production in macrophages - Guo, Meiliang; Zhuang, Haojun; Su, Yimin; Meng, Qinqin; Liu, Wanwen; Liu, Na; Wei, Min; Dai, Sheng-Ming; Deng, Hui (Frontiers in Immunology, 2023)
Current evidence suggests that IL-23, IL-6, and TNF-α play pivotal roles in the pathogenesis of psoriasis. Although it has been established that Sirtuin 3 (SIRT3) mediates the inflammatory process, the underlying mechanisms remain largely unclear. Herein, we substantiated that the inhibition or deletion of SIRT3 increased the acetylation level of spliced form of X-box binding protein 1 (XPB1s), enhancing its transcriptional activity and IL-23a production. Pharmacologically inhibition of XBP1s with MKC8866 downregulated the expression of inflammatory cytokines in SIRT3-inhibited or Sirt3-KO BMDMs stimulated by IMQ. Inhibition or knockdown of SIRT3 could exacerbate psoriasis-like skin inflammation in an imiquimod-induced psoriasis-like mouse model. Besides, a decrease in SIRT3 expression was observed in the macrophages of psoriasis patients, which increased the expression and acetylation level of XBP1s. Overall, we provide compelling evidence of the crucial role of SIRT3 in the IL-23 axis in psoriatic inflammation and novel molecular insights into the anti-inflammatory effects of SIRT3.